Exam Ref MD-101 Managing Modern Desktops, 2nd Edition - Bettany, Andrew; Warren, Andrew (Microsoft Press, 2021)
Prepare for Microsoft Exam MD-101 and help demonstrate your real-world mastery of skills and knowledge required to manage modern Windows 10 desktops. Designed for Windows administrators, Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified Associate level. Focus on the expertise measured by these objectives: Deploy and upgrade operating systems Manage policies and profiles Manage and protect devices Manage apps and data This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you have experience deploying, configuring, securing, managing, and monitoring devices and client applications in an enterprise environment About the Exam Exam MD-101 focuses on knowledge needed to plan a Windows 10 deployment; plan and implement Windows 10 with Windows Autopilot and MDT; manage accounts, VPN connections, and certificates; implement device compliance policies; configure device profiles; manage user profiles; implement and manage device, application, and threat protection; manage Intune devices; monitor devices; manage updates; deploy/update applications; and implement Mobile Application Management (MAM). About Microsoft Certification Passing this exam and Exam MD-100: Windows 10 fulfills your requirements for the Microsoft 365 Certified: Modern Desktop Administrator Associate certification credential, demonstrating your ability to deploy, configure, secure, manage, and monitor devices and client applications in an enterprise environment. See full details at: microsoft.com/learn.